A "whole pot" strategy for root growth quantification or microbiota-root interaction studies. (August 2017) - Xu, Xin; Robb, Jane; Nazar, Ross N.
Abstract: By using a wilt pathogen-tomato pathosystem as a model, we have developed a direct method to extract whole pot soil samples for PCR-based quantification of roots or the root microbiota. This approach eliminates a need for root harvesting or further DNA purification. The pot contents are simply freeze dried and disrupted with a high-speed blender prior to extraction with SDS-phenol, in the presence of milk powder to minimize adsorption losses, and internal control templates to correct for losses and inhibiting compounds. After suitable dilution, this DNA extract can be assayed directly by PCR amplification. The method is rapid, cost efficient and, when combined with suitable specific-primers and internal controls, can be applied to the quantification of essentially any root and/or colonizing pathogen for bioassays of soil phenomena. Highlights: Method to extract whole pot soil samples for PCR-based quantification of roots or the root microbiota. Eliminates a need for root harvesting. Applicable to the quantification of any root and/or colonizing pathogen for bioassays. Rapid and cost effective.